2020
DOI: 10.3390/toxins12120736
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Binding Domains of TcdB from Clostridioides difficile for Chondroitin Sulfate Proteoglycan-4 and Frizzled Proteins Are Functionally Independent and Additive

Abstract: Toxin B (TcdB) produced by Clostridioides difficile is a main pathogenicity factor that affects a variety of different cell types within the colonic mucosa. TcdB is known to utilize frizzled-1,2,7 and chondroitin sulfate proteoglycan-4 (CSPG4) as protein receptors. By using human cervical cancer cell line HeLa CSPG4 knockout (CSPG4−/−) cells as well as TcdB mutants which do not bind to either CSPG4 or frizzled-1,2,7, or both, we evaluated the impact of the individual receptors for cytopathic and cytotoxic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…The binding of TcdB to CSPG4 receptor induces cell rounding and apoptosis in HeLa and HT29 cells at picomolar concentrations of TcdB, while binding of TcdB to CSPG4 receptor mediate necrotic effects at higher concentration of TcdB. 70 72 The binding of TcdB to PVRL3 receptor induces necrosis cell death at high concentrations (the nanomolar range) of TcdB. 70 , 72 , 73 The FZD functions as an alternative receptor to CSPG4; indeed the binding of TcdB to FZD receptor induces cytopathic effects and apoptosis at picomolar concentrations of TcdB.…”
Section: Molecular Characteristics Of Tcda and Tcdbmentioning
confidence: 99%
See 3 more Smart Citations
“…The binding of TcdB to CSPG4 receptor induces cell rounding and apoptosis in HeLa and HT29 cells at picomolar concentrations of TcdB, while binding of TcdB to CSPG4 receptor mediate necrotic effects at higher concentration of TcdB. 70 72 The binding of TcdB to PVRL3 receptor induces necrosis cell death at high concentrations (the nanomolar range) of TcdB. 70 , 72 , 73 The FZD functions as an alternative receptor to CSPG4; indeed the binding of TcdB to FZD receptor induces cytopathic effects and apoptosis at picomolar concentrations of TcdB.…”
Section: Molecular Characteristics Of Tcda and Tcdbmentioning
confidence: 99%
“… 70 72 The binding of TcdB to PVRL3 receptor induces necrosis cell death at high concentrations (the nanomolar range) of TcdB. 70 , 72 , 73 The FZD functions as an alternative receptor to CSPG4; indeed the binding of TcdB to FZD receptor induces cytopathic effects and apoptosis at picomolar concentrations of TcdB. 70 , 72 , 74 Another important peculiarity of TcdB is that TcdB can bind to the membrane receptor with amino acid sequences that extend beyond the CROP sequences.…”
Section: Molecular Characteristics Of Tcda and Tcdbmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is believed that TcdB could use multiple receptors at the same time or have specific receptors for different cell types. Recent studies also found TcdB variants derived from different strains show varied binding affinities to the above receptors (Chung et al, 2018;Henkel et al, 2020;Lopez-Urena et al, 2019;Mileto et al, 2020). Surprisingly, TcdB from hypervirulent 027 strain has low affinity to FZDs and PVRL3, which are expressed in epithelial cells, leading to the hypothesis that this TcdB variant may use other unknown receptors for cell entry.…”
Section: Introductionmentioning
confidence: 99%